The role of Hinduism and Islam in the liberation of South Africa : the limpopo perspective (1970-1994) - Langa, Mmaphuti Felicia (My University, 2016)
Refer to document
Thesis (M.A. (International Politics)) --University of Limpopo, 2016
Keywords: Faith; Religion; Hinduism; Faith; Africa -- Religion